Financial Service Technology in Indonesia: Between Free Market Regime and Consumer Protection - Hamzah Hamzah (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
The free market era provided uninterrupted traffic in goods and services throughout the world, and was initially formed to offer benefits. Although there were still protests in technical problems and rising disputes that led a sue to legal institutions, countries agreed to maintain the free market. As a counterpart, the free market cannot ignore consumer’s protection as a standard of service. The liability development between consumer and producer relationship arranged from caveat emptor, to caveat vendor and finally to strict liability in the consumer protection system, implies disclosure of information on products and services. This research faces the legal theory of a free market regime with the theory of consumer’s protection law. This research proceeds to discuss two main issues. The first issue is an essential of Financial Technology or Fin-tech of services. The second issues is the influence of Fin-tech on the free market and consumer protection. Research uses a normative legal research method and the data obtained are secondary data from literary sources such as literature, articles and internet sites. Results of the analysis shows; first, the free market regime is both an opportunity as well as a challenge, therefore it is still worth to maintain. The consumer protection’s regime is the balance point of the free market’s regime. Theoretically, consumer’s protection must be used as a tool to protect the consumer’s interests. Moreover, it could manage the behaviour of service providers. Secondly, the role of the Financial Services Authority is a key to ensuring that balance is still on maintained. Supervision and determination of financial service providers broadly provide information for the public to choose carefullyof their necessity financial services